Uniqki: A Personal Wiki Builder
A Uniqki site

Convolution theorem

Let $\mathfrak{F}$, $*$, and $\cdot$ denote the Fourier transform, convolution, and point-wise multiplication, respectively. The convolution theorem states \begin{equation} \mathfrak{F}\{f*g\}=\mathfrak{F}\{f\}\cdot\mathfrak{F}\{g\} \label{eq:convolution} \end{equation} and \begin{equation} \mathfrak{F}\{f\cdot g\}=\mathfrak{F}\{f\}*\mathfrak{F}\{g\}. \label{eq:multiplication} \end{equation}

1   Proof using the shift theorem

The left-hand side of Eq. \eqref{eq:convolution} is \begin{equation} \begin{split} \mathfrak{F}\{f*g\}(u) &=\int_{-\infty}^\infty f(x)*g(x)\,e^{-2i\pi ux}\,dx\\ &=\int_{-\infty}^\infty\int_{-\infty}^\infty f(y)g(x-y)\,dy\,e^{-2i\pi ux}\,dx\\ &=\int_{-\infty}^\infty\int_{-\infty}^\infty f(y)g(x-y)e^{-2i\pi ux}\,dy\,dx\\ &=\int_{-\infty}^\infty\int_{-\infty}^\infty f(y)g(x-y)e^{-2i\pi ux}\,dx\,dy\\ &=\int_{-\infty}^\infty f(y)\int_{-\infty}^\infty g(x-y)e^{-2i\pi ux}\,dx\,dy. \end{split} \label{eq:convolution_proof_shift} \end{equation}

Let $F=\mathfrak{F}\{f\}$ and $G=\mathfrak{F}\{g\}$. By the shift theorem, the inner integral $\int_{-\infty}^\infty g(x-y)e^{-2i\pi ux}\,dx=e^{-2i\pi uy}G(u)$ and Eq. \eqref{eq:convolution_proof_shift} reduces to \begin{equation} \begin{split} \mathfrak{F}\{f*g\}(u) &=\int_{-\infty}^\infty f(y)e^{-2i\pi uy}G(u)\,dy\\ &=\int_{-\infty}^\infty f(y)e^{-2i\pi uy}\,dy\,G(u)\\ &=F(u)\cdot G(u)\\ &=\mathfrak{F}\{f\}(u)\cdot\mathfrak{F}\{g\}(u). \end{split} \label{eq:convolution_proof_2_shift} \end{equation} where $F(u)=\mathfrak{F}\{f\}(u)$.

By taking the inverse Fourier transform of both sides of Eq. \eqref{eq:multiplication}, we obtain \begin{equation} \begin{split} [f\cdot g](x) &=\mathfrak{F}^{-1}\{F*G\}(x)\\ &=\int_{-\infty}^\infty F(u)*G(u)\,e^{2i\pi ux}\,du\\ &=\int_{-\infty}^\infty\int_{-\infty}^\infty F(y)G(u-y)\,dy\,e^{2i\pi ux}\,du\\ &=\int_{-\infty}^\infty\int_{-\infty}^\infty F(y)G(u-y)\,e^{2i\pi ux}\,dy\,du\\ &=\int_{-\infty}^\infty\int_{-\infty}^\infty F(y)G(u-y)\,e^{2i\pi ux}\,du\,dy\\ &=\int_{-\infty}^\infty F(y)\int_{-\infty}^\infty G(u-y)\,e^{2i\pi ux}\,du\,dy. \end{split} \label{eq:multiplication_proof_shift} \end{equation}

By the shift theorem, the inner integral $\int_{-\infty}^\infty G(u-y)\,e^{2i\pi ux}\,du=e^{2i\pi yx}g(x)$ and Eq. \eqref{eq:multiplication_proof_shift} reduces to \begin{equation} \begin{split} [f\cdot g](x) &=\int_{-\infty}^\infty F(y)e^{2i\pi yx}g(x)\,dy\\ &=\int_{-\infty}^\infty F(y)e^{2i\pi yx}\,dy\,g(x)\\ &=f(x)\cdot g(x). \end{split} \label{eq:multiplication_proof_2_shift} \end{equation}

2   Proof using Fubini’s theorem

The left-hand side of Eq. \eqref{eq:convolution} is \begin{equation} \begin{split} \mathfrak{F}\{f*g\}(u) &=\int_{-\infty}^\infty f(x)*g(x)\,e^{-2i\pi ux}\,dx\\ &=\int_{-\infty}^\infty\int_{-\infty}^\infty f(y)g(x-y)\,dy\,e^{-2i\pi ux}\,dx.\\ \end{split} \label{eq:convolution_proof_fubini} \end{equation}

By letting $x’=x-y$ and using Fubini’s theorem, Eq. \eqref{eq:convolution_proof_fubini} can be written as \begin{equation} \begin{split} \mathfrak{F}\{f*g\}(u) &=\int_{-\infty}^\infty\int_{-\infty}^\infty f(y)g(x’)\,dy\,e^{-2i\pi u(x’+y)}\,dx’\\ &=\int_{-\infty}^\infty f(y)e^{-2i\pi uy}\,dy\int_{-\infty}^\infty g(x’)e^{-2i\pi ux’}\,dx’\\ &=\mathfrak{F}\{f\}(u)\cdot\mathfrak{F}\{g\}(u). \end{split} \label{eq:convolution_proof_2_fubini} \end{equation}

Let $F=\mathfrak{F}\{f\}$ and $G=\mathfrak{F}\{g\}$. By taking the inverse Fourier transform of both sides of Eq. \eqref{eq:multiplication}, we obtain \begin{equation} \begin{split} [f\cdot g](x) &=\mathfrak{F}^{-1}\{F*G\}(x)\\ &=\int_{-\infty}^\infty F(u)*G(u)\,e^{2i\pi ux}\,du\\ &=\int_{-\infty}^\infty\int_{-\infty}^\infty F(y)G(u-y)\,dy\,e^{2i\pi ux}\,du.\\ \end{split} \label{eq:multiplication_proof_fubini} \end{equation}

Similarly, by letting $u’=u-y$ and using Fubini’s theorem, Eq. \eqref{eq:multiplication_proof_fubini} can be written as \begin{equation} \begin{split} [f\cdot g](x) &=\int_{-\infty}^\infty\int_{-\infty}^\infty F(y)G(u’)\,dy\,e^{2i\pi(u’+y)x}\,du’\\ &=\int_{-\infty}^\infty F(y)e^{2i\pi y x}\,dy\int_{-\infty}^\infty G(u’)e^{2i\pi u’x}\,du’\\ &=f(x)\cdot g(x). \end{split} \label{eq:multiplication_proof_2_fubini} \end{equation}